Valorization of lubricant-based wastewater for bacterial neutral lipids production: Growth-linked biosynthesis. (15th September 2016) - Da Silva, Pedro D.M.P.; Lima, Filipa; Alves, Maria Madalena; Bijmans, Martijn F.M.; Pereira, Maria Alcina
Abstract: Lipids produced by microorganisms are currently of great interest as raw material for either biofuels or oleochemicals production. Significant biosynthesis of neutral lipids, such as triacylglycerol (TAG) and wax esters (WE) are thought to be limited to a few strains. Hydrocarbonoclastic bacteria (HCB), key players in bioremediation of hydrocarbon contaminated ecosystems, are among this group of strains. Hydrocarbon rich wastewaters have been overlooked concerning their potential as raw material for microbial lipids production. In this study, lubricant-based wastewater was fed, as sole carbon source, to two HCB representative wild strains: Alcanivorax borkumensis SK2, and Rhodococcus opacus PD630. Neutral lipid production was observed with both strains cultivated under uncontrolled conditions of pH and dissolved oxygen. A. borkumensis SK2 was further investigated in a pH- and OD-controlled fermenter. Different phases were assessed separately in terms of lipids production and alkanes removal. The maximum TAG production rate occurred during stationary phase (4 mg-TAG/L h). The maximum production rate of WE-like compounds was 15 mg/L h, and was observed during exponential growth phase. Hydrocarbons removal was 97% of the gas chromatography (GC) resolved straight-chain alkanes. The maximum removal rate was observed during exponential growth phase (6 mg-alkanes/L h). This investigation proposes a novel approach for the management of lubricant waste oil, aiming at its conversion into valuable lipids. The feasibility of the concept is demonstrated under low salt (0.3%) and saline (3.3%) conditions, and presents clues for its technological development, since growth associated oil production opens the possibility for establishing continuous fermentation processes. Graphical abstract: Highlights: Alcanivorax borkumensis SK2 and Rhodococcus opacus PD630 produce neutral lipids from real wastewater. Oil-rich wastewater valorization is possible in either low or high salt conditions. Production of Wax Esters-like compounds by A . borkumensis SK2, is cell growth related. Hydrocarbons removal was 97% of the gas chromatography-resolved straight-chain alkanes.